Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.jasms.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for measuring conformation of solvent-disrupted protein subunits using T-WAVE ion mobility MS: An investigation into eukaryotic initiation factors

Abstract: The methodology developed in the research presented herein makes use of chaotropic solvents to gently dissociate subunits from an intact macromolecular complex and subsequently allows for the measurement of collision cross section (CCS) for both the recombinant (R-eIF3k) and solvent dissociated form of the subunit (S-eIF3k). In this particular case, the k subunit from the eukaryotic initiation factor 3 (eIF3) was investigated in detail. Experimental and theoretical CCS values show both the recombinant and solv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
69
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 35 publications
(34 reference statements)
3
69
1
Order By: Relevance
“…The simultaneous measurement of Ω values of both the intact complex and disassembly products generates structural restraints which are then used for calculating topological models of the protein complexes. The basic assumption underlying this methodology is that the generated subcomplexes retain their native-like confirmations, and indeed recent studies have demonstrated that the solution structure of the disassembly products is maintained and no major rearrangement in either solution or gas phases have occurred 4,6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simultaneous measurement of Ω values of both the intact complex and disassembly products generates structural restraints which are then used for calculating topological models of the protein complexes. The basic assumption underlying this methodology is that the generated subcomplexes retain their native-like confirmations, and indeed recent studies have demonstrated that the solution structure of the disassembly products is maintained and no major rearrangement in either solution or gas phases have occurred 4,6 .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent IM studies of both individual proteins 2,3 and non-covalent protein complexes [4][5][6][7][8][9] , successfully demonstrated that protein quaternary structure is maintained in the gas phase, and highlighted the potential of this approach in the study of protein assemblies of unknown geometry. Here, we provide a detailed description of IMS-MS analysis of protein complexes using the Synapt (Quadrupole-Ion Mobility-Time-of-Flight) HDMS instrument (Waters Ltd; the only commercial IM-MS instrument currently available) 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, protein ions display a distribution of charge states when produced through nESI, and IM and MS measurements indicate that ions having the lowest ionic charge are the most "native-like" [11,13,24], in that IM data for ions of low charge states are, in general, the most-correlated to X-ray and nuclear magnetic resonance (NMR) datasets [25][26][27] and are often the most useful data points when constraining topological models of multiprotein complexes from IM-MS data [16]. For example, in early experiments involving tryptophan-RNA binding attenuation protein (TRAP) 11-mer ions, higher charge states were observed to be more compact relative to ions having lower charge [13].…”
Section: Introductionmentioning
confidence: 99%
“…For example, solution-phase disruption approaches for producing low charge state protein monomers for IM-MS measurements is currently the dominant approach to the problem; however, such data collection requires extensive screening of solution conditions to remove subunit proteins from the assembly without significant remodeling or unfolding [9,12,[18][19][20][21][22][23]. An alternative method for generating IM information on compact protein subunits is through gas-phase dissociation.…”
mentioning
confidence: 99%